Corak Fikih Dalam Tafsir An-Nur Karya Hasbi Ash-Shiddieqy - Andieni Putri Olivia; Kiki Muhammad Hakiki; Abuzar Al-Ghifari (Institut Agama Islam Sumatera Barat, 2024)
The interpretation that arose in the 19th century with a distinct approach from earlier texts provided the foundation for this investigation. This study aims to pinpoint the characteristics of Hasbi Ash-Shiddieqy's fiqh interpretation style in Tafsir An-Nur. Additionally, the research utilizes a qualitative method through a literature review approach. Therefore, according to the results of this study, Hasbi Ash-Shiddieqy is recognized as a productive mufassir from Aceh, respected among educators, scholars, and reformist thinkers. Secondly, by using the tafsir as a tool for da'wah in simple language, it became more widely accepted among the community. Thirdly, among various approaches to interpreting tafsir works, Hasbi's tafsir falls into the fiqh category. This is evidenced by his emphasis on interpreting legal verses, which he dedicates a larger portion to compared to other types of verses.